An Investigation of Tone Perception and Production in German Learners of Mandarin - DING, Hongwei; HOFFMANN, Rudiger; JOKISCH, Oliver (Archives of Acoustics, 2011)
This study investigates the possible errors related to Mandarin tone perception and production by German speakers. In a preliminary test, 23 German listeners should identify the tones of 186 monosyllables. Results show that exposure to Man- darin Chinese can help to discriminate lexical tones as highly expected. In the main experiment, 17 German subjects were asked to take part in a perception and pro- duction test. Stimulus of perception involves 48 monosyllables uttered by a standard professional Chinese speaker; acoustic measures were conducted to analyze the pro- duction of 72 monosyllables for each subject. It is found that German speakers have much smaller f0 range than Chinese native speakers. Findings can provide implications for cross language studies and teaching practices.